A facile method to incorporate tetraphenylethylene into polymeric amphiphiles: High emissive nanoparticles for cell-imaging. (January 2019) - Ding, Lan; Zhou, Shixin; Li, Dahua; Wu, Chengfeng; Xing, Yuzhi; Song, Bo
Abstract: Encapsulating fluorogens into polymeric nanoparticles is proven an effective method to shield the fluorogens from the outer environment and improve the biocompatibility as well. Conventionally, the fluorogens are firstly conjugated to the monomers and then polymerized into macromolecules, where tedious molecular design and synthesis was unavoidable. Herein, we present a facile method to prepare the fluorogen-functionalized polymer, and then use the polymer as build blocks to fabricate nano-probes aiming at cell-imaging. Unlike the conventional ways, we prepared a homopolymer with active esters on the repeating units and used the polymer as matrix to graft fluorogens and hydrophilic groups. Note that the fluorogen and hydrophilic groups selected in our study were tetraphenylethylene (TPE) and polyethylene glycol (PEG), respectively. The resulting amphiphilic random copolymer self-assembled into spherical nanoparticles with size around 225 nm in aqueous solution. With comparable amount of TPE moieties, the polymeric nanoparticles demonstrated much stronger emission than the nanoparticles formed by small molecules of TPE derivatives. The polymeric nanoparticles showed very good stability and biocompatibility, and were employed to label Hela cells and gave high-contrast fluorescent images. We anticipate that the methodology presented in this study might be developed into a general avenue to encapsulating fluorogens into nanoparticles. Graphical abstract: Image 1 Highlights: Post-polymerization modification was employed to prepare amphiphilic copolymers. The copolymer contains TPE and PEG groups on the side chain. The nanoparticles formed by the copolymers showed strong fluorescent emission. The nanoparticles were applied to label Hela cells with high-contrast images.